ANALISIS PERBEDAAN PERILAKU ETIS PELAKU AKUNTANSI DALAM ETIKA PENYUSUNAN LAPORAN KEUANGAN SATUAN KERJA PERANGKAT DAERAH KABUPATEN BADUNG - Handayani, IGAA. Rai Utami; Ratnadi, Ni Made Dwi; Putri, IGAM Asri Dwija (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2017)
The aim of this study was to analyze the differences in accounting principals of ethical behavior based on the individual characteristics of the ethics of the financial statements of the local work force. Methods of data collection using questionnaire techniques. This study uses analysis  techniques Mann Whitney U - Test. The result is the behavior of agents belonging to the category of accounting internal locus of control is more ethical than external locus of control. The behavior of agents accounting including senior category no more than ethical the juniors in the ethics of the financial statements of the local work. Accounting actor's behavior women are not more  ethical than men. The behavior of agents accounting category benevolents more ethical than entitleds. The behavior of agents accounting educational background in accounting is no more ethical than non ethical accounting in preparing the financial statements of the local work force.
Keywords: ethical behavior, locus of control, length of service, gender, equity sensitivity, background education